Peranan Sistem Informasi Dalam Pelayanan Kesehatan di Puskesmas Kedungdoro Surabaya - Slamet Imam Syafii; Rina Dewi; Achmad Daengs GS (Universitas 45 Surabaya, 2024)
Information systems have an important role in various fields including in the field of health services in various community health centers (Puskesmas) in various regions in Indonesia. Information systems can contribute to accelerating and simplifying the flow of services to patients. The results of the KKL reported that the role of the information system in the Puskesmas Kedungdoro Surabaya can be a bridge of connectivity between patients, health workers and the service system implemented so that it can support health service activities running according to the target achievement. An important task that must be carried out by the Puskesmas Kedungdoro is to continuously educate patients to foster understanding in the service system at the Puskesmas Kedungdoro Surabaya.